Title: Expansion of a national differentiated service delivery model to support people living with HIV and other chronic conditions in South Africa: a descriptive analysis - Liu, Lingrui; Christie, Sarah; Munsamy, Maggie; Roberts, Phil; Pillay, Merlin; Shenoi, Sheela V; Desai, Mayur M; Linnander, Erika L (BMC health services research, 2021)
South Africa is home to 7.7 million people living with HIV and supports the largest antiretroviral therapy (ART) program worldwide. Despite global investment in HIV service delivery and the parallel challenge of non-communicable diseases (NCDs), there are few examples of integrated programs addressing both HIV and NCDs through differentiated service delivery. In 2014, the National Department of Health (NDoH) of South Africa launched the Central Chronic Medicines Dispensing and Distribution (CCMDD) program to provide patients who have chronic diseases, including HIV, with alternative access to medications via community-based pick-up points. This study describes the expansion of CCMDD toward national scale. Yale monitors CCMDD expansion as part of its mixed methods evaluation of Project Last Mile, a national technical support partner for CCMDD since 2016. From March 2016 through October 2019, cumulative weekly data on CCMDD uptake [patients enrolled, facilities registered, pick-up points contracted], type of medication provided [ART only; NCD only; and ART-NCD] and collection sites preferred by patients [external pick-up points; adherence/outreach clubs; or facility-based fast lanes], were extracted for descriptive, longitudinal analysis. As of October 2019, 3,436 health facilities were registered with CCMDD across 46 health districts (88 % of South Africa's districts), and 2,037 external pick-up points had been contracted by the NDoH. A total of 2,069,039 patients were actively serviced through CCMDD, a significant increase since 2018 (p < 0.001), including 76 % collecting ART [64 % ART only, 12 % ART plus NCD/comorbidities] and 479,120 [24 %] collecting medications for chronic diseases only. Further, 734,005 (35 %) of patients were collecting from contracted, external pick-up points, a 73 % increase in patient volume from 2018. This longitudinal description of CCMDD provides an example of growth of a national differentiated service delivery model that integrates management of HIV and noncommunicable diseases. This study demonstrates the success of the program in engaging patients irrespective of their chronic condition, which bodes well for the potential of the program to address the rising burden of both HIV and NCDs in South Africa. The CCMDD program expansion signals the potential for a differentiated service delivery strategy in resource-limited settings that can be agnostic of the patients chronic disease condition.